Rancang Bangun Sistem Voucher Wi-fi Jaringan Mikrotik Menggunakan Aplikasi Mikhmon di SMK Tahsinul Akhlaq Kalibagor Situbondo - Rahmat Shofan Razaqi; Nur Azizah (Departement of Mathematics Education, 2024)
In the development of increasingly sophisticated computer science, computer network science experiences many challenges in various aspects of people's lives which are already interconnected with each other. This challenge develops along with the needs of the wider community who must be connected to the internet network in various aspects of life. One of the challenges is the need for a computer network system that can provide internet services at a certain rate and timeframe. One application that can answer this challenge is the Mikhmon application. This application can Generate Wifi-Vouchers containing Usernames and Passwords for Users to log into the Mikrotik network that can accommodate internet fees or tariffs and set a certain grace period for Users to connect to the Mikrotik-based internet network. The Mikrotik network has been proven to be a computer network system structure or internet network that is affordable and quite reliable. Mikrotik as a system also has many options in producing routers. In this study, we will use the Mikrotik RB941-2nd Haplite router, where this router really needs the Mikhmon application as a replacement application for the User Manager on the Mikrotik router with a more expensive version. Therefore, the authors propose the title of this research so that it can be expected to become a discourse later for the community who will make a computer network system that is cheap and has good service performance.